"Causes Of Unemployment in the Modern Economy and Ways to Eliminate it" - Ashraf Qurbonaliyevich Abdualimov; Yuldashev Behruz Behzod ugli (Zien Journals, 2022)
This article analyzes the causes, factors, and measures to combat unemployment, which is one of the most pressing issues in each country, and how important they are
Keywords: Economy; cyclical; unemployment; employment